(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
The Summer Course in Biotechnology, promoted by the Postgraduate Program in Biotechnology (PPG-Biotec) at UNIFESP, held its fourth edition in 2024, bringing together students, alumni, and professionals interested in the field. Over the course of two weeks, participants had access to lectures, panel discussions, and engaged in mini experimental projects. With 25 participants students, the event received positive feedback, standing out as a space for learning and scientific dissemination. Furthermore, the experience of the organizing team was one of learning and overcoming challenges, emphasizing the importance of collaboration and strategic planning for the event’s success. This synergy between organizers and participants strengthens the course’s purpose as a platform for knowledge promotion and research stimulation in the field of biotechnology.